Een vergeten verjaardag: de eerste Europese hypermarkten openen in Brussel in 1961 - Jean-Pierre Grimmeau (Brussels Studies)
Hypermarkets are self-service shops with a surface area of more than 2 500 m², which sell food and non food products, are located on the outskirts of a city, are easily accessible and have a large car park. They are generally considered to have been invented in France in 1963 (Carrefour in Sainte-Geneviève-des-Bois, close to Paris, 2 500 m²). But nearly two years earlier, in 1961, GB had opened three hypermarkets under the name of SuperBazar, in Bruges, Auderghem and Anderlecht, measuring between 3 300 and 9 100 m². Through an examination of the literature, an exploration of GIB archives and the stories of stakeholders in the Belgian distribution sector, the article compares in detail the history of the first Belgian and French hypermarkets, which has never been done before. If we do not consider the Bruges location of only 3 300 m², which was initially designed as a department store, the point of sale in Auderghem (9 100 m² Boulevard du Souverain), based on the American model of the discount department store but associated with an integrated supermarket, must be considered as the first European hypermarket. Even if the association of food and non food products under the same roof was unusual in the United States, it nevertheless existed. Hypermarkets are therefore an American invention, GB opened the first European hypermarkets in Belgium and Carrefour spread the model of the hypermarket throughout the world, taking over most of the Belgian hypermarkets in 2000.